Effects of roxadustat on anemia, iron metabolism, and lipid metabolism in patients with non-dialysis chronic kidney disease - Hirai, Keiji; Kaneko, Shohei; Minato, Saori; Yanai, Katsunori; Hirata, Momoko; Kitano, Taisuke; Ito, Kiyonori; Ueda, Yuichiro; Ookawara, Susumu; Morishita, Yoshiyuki (Frontiers in Medicine, 2023)
Background We determined the effects of roxadustat on the values of anemia, iron metabolism, renal function, proteinuria, and lipid metabolism and identified the associated factors of the change in hemoglobin levels after roxadustat administration in non-dialysis chronic kidney disease (CKD) patients who were receiving an erythropoietin-stimulating agent (ESA). Methods We conducted retrospective analysis of the changes in hemoglobin, serum ferritin, total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and triglyceride levels; transferrin saturation; the estimated glomerular filtration rate; and the urinary protein/creatinine ratio over 24 weeks after the change from an ESA to roxadustat in 50 patients with non-dialysis CKD and anemia (roxadustat group). Seventy-two patients with non-dialysis CKD and anemia who proceeded ESA therapy were used as the control (ESA) group. Results We observed no significant between-group differences in clinical parameters at baseline except for the significantly lower hemoglobin concentration and lower proportion of diabetes mellitus in the roxadustat group. The hemoglobin concentration was significantly higher in the roxadustat group after 24 weeks (11.3 ± 1.2 versus 10.3 ± 1.0 g/dL; value of p < 0.05), whereas the transferrin saturation, ferritin concentration, estimated glomerular filtration rate, and urinary protein/creatinine ratio were not different between the two groups. TC (135.9 ± 40.0 versus 165.3 ± 38.4 mg/dL; value of p < 0.05), LDL-C (69.1 ± 28.3 versus 87.2 ± 31.5 mg/dL; value of p < 0.05), HDL-C (41.4 ± 13.5 versus 47.2 ± 15.3 mg/dL; value of p < 0.05), and triglyceride concentrations (101.5 ± 52.7 versus 141.6 ± 91.4 mg/dL, value of p < 0.05) were significantly lower in the roxadustat group compared with the ESA group at 24 weeks. Multiple linear regression analysis showed that the roxadustat dose at baseline (standard coefficient [β] = 0.280, value of p = 0.043) was correlated with the change in the hemoglobin levels during the first 4 weeks of roxadustat treatment, whereas age (β = 0.319, value of p = 0.017) and the roxadustat dose at 24 weeks (β = −0.347, value of p = 0.010) were correlated with the hemoglobin concentration after 24 weeks of roxadustat administration. Conclusion Roxadustat can improve anemia and reduce serum cholesterol and triglyceride levels in non-dialysis CKD patients after the patients’ treatment was switched from an ESA without affecting renal function or proteinuria. These results indicate that roxadustat has superior effects to ESAs regarding anemia and lipid metabolism at the dose selected for the comparison in patients with non-dialysis CKD.